ROLE OF GENETIC FACTORS IN THE DEVELOPMENT OF CLOPIDOGREL RESISTANCE AMONG PATIENTS REFERRED FOR PERCUTANEOUS CORONARY INTERVENTIONS - S. T. Matskeplishvili; E. B. Prokhorchuk; Ya. E. Arutyunova; I. V. Koksheneva; L. S. Shakhnazaryan; B. R. Sandukhadze; K. G. Skryabin; A. V. Melerzanov; Yu. I. Buziashvili (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations between genetic polymorphisms and the development of clopidogrel resistance in patients referred for percutaneous coronary interventions (PCI).Material and methods. The study included 84 patients with coronary heart disease (CHD), who underwent planned PCI. Dynamic assessment of platelet aggregation was performed using light transmission aggregometry method (two-channel laser analyser Biola-230LA). The role in the development of inadequate suppression of platelet aggregation during the standard-dose dual antiplatelet therapy (DAT) was investigated for the following genes and polymorphic alleles: CYP2C19 (rs4244285*2, rs4986893*3, rs28399504*, rs56337013*5, and rs12248560*17); CYP2C9 (rs1057910*3); CYP3A4 (rs2242480); CYP2B6 (rs3211371 (5*); CYP3A5 (rs28365083*2 and rs776746); and CYP1A2 (rs762551).Results. The two study groups demonstrated a statistically significant difference in the prevalence of CYP2C19 rs4244285 (2*) polymorphisms, with an increase in GA and AA genotypes and a reduction in the “wild” GG genotype (Χ2 =11,7; р=0,003). The GA genotype was associated with inadequate suppression of platelet aggregation in patients receiving clopidogrel (75 mg/d) and aspirin (300 mg/d; odds ratio 6,27; 95% confidence interval 1,8–21,69). No significant inter-group differences were observed for other polymorphisms (CYP2C9 (rs1057910*3); CYP3A4 (rs2242480); CYP2B6 (rs3211371 (5*)); CYP3A5 (rs28365083*2, rs776746); and CYP1A2 (rs762551)).Conclusion. The degree of platelet aggregation in patients on DAT is related to their genetic status. The assessment of genetic polymorphisms can facilitate the choice of optimal therapeutic strategies in clopidogrel-resistant patients. Patients with the CYP2C192* polymorphism are in particular need for an additional correction of the antiaggregant treatment scheme.